Double‐hybrid density functionals. (25th July 2014) - Goerigk, Lars; Grimme, Stefan
Abstract : Double‐hybrid density functionals (DHDFs) are reviewed in this study. In DHDFs parts of conventional density functional theory (DFT) exchange and correlation are replaced by contributions from nonlocal Fock‐exchange and second‐order perturbative correlation. The latter portion is based on the well‐known MP2 wave‐function approach in which, however, Kohn–Sham orbitals are used to calculate its contribution. First, related methods preceding this idea are reviewed, followed by a thorough discussion of the first modern double‐hybrid B2‐PLYP. Parallels and differences between B2‐PLYP and its various successors are then outlined. This discussion is rounded off with representative thermochemical examples demonstrating that DHDFs belong to the most robust and accurate DFT approaches currently available. This analysis also presents hitherto unpublished results for recently developed DHDFs. Finally, how double‐hybrids can be combined with linear‐response time‐dependent DFT is also outlined and the value of this approach for electronically excited states is shown. WIREs Comput Mol Sci 2014, 4:576–600. doi: 10.1002/wcms.1193 This article is categorized under: Electronic Structure Theory > Density Functional Theory Abstract :